Effects and Implications of Drug Abuse on Students’ Attitude to Learning in Federal College of Education Technical, Gombe, Nigeria - Abdullahi Sani Nuhu; Umar Ibrahim; Jamil Mika'il Yahya; Idris Aliyu; Ibrahim Umar; Mohammed Dodo Kwairanga; Pate Hauwa Baba; Haruna Yusuf; Abubakar A. Dahiru (Sociometry Journal of Social Science, Art and Humanity, 2021)
Drug Abuse is a physical and physiological disorder often resulting from persistent and excessive self-administration of drugs without regard to medically and culturally acceptable patterns. This research focuses on the effects and implications of drug abuse on students' attitudes to learning in the Federal College of Education Technical, Gombe. The resultant effects of this menace could be physical, social, psychological, and mental, while the implication reflects mainly the student's cognitive, psychomotor, and affective domains of learning. The most commonly abused drugs by students are types of Amphetamine, one of which is tramadol, popularly known as Tramol, and types of Inhalants. The effect is pervasive among adolescent and middle-late childhood youth. The common causes of this menace include peer group, lack of proper parental care and supervision, coping with the pressure of life, and making forget problems. In comparison, some of the signs and symptoms are the unusual use of dark glasses, odor neutralizers such as perfume, air fresheners, and chewing gum. There is a significant relationship between drug abuse and students' attitude to learning. Therefore, it recommends that the college authorities organize periodic or routine seminars and workshops for students on campus. The topic should include health education and counseling, among others, and to request the Government to impose heavy tax on any industry involved in producing such illicit drugs.